2018
DOI: 10.1016/j.juro.2018.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Family History is Underestimated in Children with Isolated Hypospadias: A French Multicenter Report of 88 Families

Abstract: Familial forms of hypospadias are far more frequent than previously reported. Even minor and isolated forms justify a full clinical investigation of the family history. Detecting these hereditary forms may help to determine the underlying genetic defects, and may improve followup and counseling of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A detailed family history, including fertility, is essential to explore possible inheritance mechanisms and to lend support for molecular genetic investigations in individuals with milder phenotypes. Phenotypic variability within families may be broad and may comprise subfertility/ infertility as the only sign, depending on the severity of the mutation (21,22).…”
Section: Family Datamentioning
confidence: 99%
“…A detailed family history, including fertility, is essential to explore possible inheritance mechanisms and to lend support for molecular genetic investigations in individuals with milder phenotypes. Phenotypic variability within families may be broad and may comprise subfertility/ infertility as the only sign, depending on the severity of the mutation (21,22).…”
Section: Family Datamentioning
confidence: 99%
“…In evaluating isolated hypospadias, which can be associated with a DSD, Ollivier et al [12] recently reported that a positive family history has been underestimated in children. Although previous studies have indicated a family history in ~10% of individuals, their study found a family history in 22% [12–14]. Thus, our findings were similar to those of previous studies assessing family history.…”
Section: Discussionmentioning
confidence: 99%
“…We collected information about potential confounding factors (CFs) associated with a higher risk of hypospadias: family history of hypospadias, [4,33] syndromic association, consanguinity, known genetic defect, [6] ART, [11,12,34] vegetarian diet, [35] and known exposure for endocrine disrupting chemicals.…”
Section: Methods 21 Study Area and Data Sourcesmentioning
confidence: 99%